Hubungan antara Konsep Diri Akademik dengan Self - Efficacy dalam Menyelesaikan Skripsi pada Mahasiswa Bimbingan dan Konseling Angkatan Universitas Ahmad Dahlan Yogyakarta - Hestiningrum, Erni (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2018)
This study aims to determine: (1) the level of Student Self Concept that is completing the thesis; (2) the level of student self-efficacy that is completing the thesis; (3) to know the relation between academic self concept and selfefficacy in completing thesis. The approach used in this research is quantitative approach with correlational type. Technique of sampling with purposive sample technique. The sample in this study 50 percent of the population, as many as 46 students. Instrument of data collection in this research use self concept academic scale as much as 38 item and self efficacy scale 36 item. Researchers use questionnaires using the likers scale in the form of Check List (√). Level of validity (validity) on the scale of self concept of academic and self efficacy are all valid (valid). Level of reliability on the scale of self-concept of academic value obtained coefficient alpha (α) of 0.922 and on the scale of self efficacy obtained coefficient value alpha (α) of 0.921.Data obtained then analyzed by using correlation analysis. The results showed that students have self-concept of academic and self efficacy in completing thesis that is high is 95.5%. That is, the higher the academic self-concept owned by students will be higher also self efficacy in completing the thesis on the students. It is based on the result of calculation of correlation with obtained p (sig) = 0.77, price p shows value greater than 0.05. So the hypothesis stating that there is a positive and significant relationship between the concept of self-academic and self-efficacy in completing the thesis on students Bimbingan Konseling Ahmad Dahlan University of Yogyakarta, accepted.